Distance education as an agent of change and development - Koul, Badri N. (1999)
Highlights the innovative features of distance education and underscores the importance of their being brought to the attention of politicians, policy makers and the society as a whole. Sketches three case studies of distance education : Mauririus, the University of the West Indies (UWI) and the Unversity of Guyana (UG).